GSK-3 Inhibition Modulates Metalloproteases in a Model of Lung Inflammation and Fibrosis - Cinetto, Francesco; Ceccato, Jessica; Caputo, Ilaria; Cangiano, Daniela; Montini, Barbara; Lunardi, Francesca; Piazza, Maria; Agostini, Carlo; Calabrese, Fiorella; Semenzato, Gianpietro; Rattazzi, Marcello; Gurrieri, Carmela; et al. (Frontiers in Molecular Biosciences, 2021)
Idiopathic Pulmonary Fibrosis (IPF) is mainly characterized by an aberrant extracellular matrix deposition, consequent to epithelial lung injury and myofibroblast activation, and inflammatory response. Glycogen Synthase Kinase 3 (GSK-3) is a serine-threonine kinase involved in several pathways and its inhibition has been already suggested as a therapeutic strategy for IPF patients. There is evidence that GSK-3 is able to induce matrix metalloproteinases (MMPs) expression and that its inhibition modulates MMP expression in the tissues. The aim of our study was to investigate the role of this GSK-3 and its inhibition in the modulation of MMP -9 and -2 in an in vivo mouse model of lung fibrosis and in vitro using different cell lines exposed to pro-inflammatory or pro-fibrotic stimuli. We found that GSK-3 inhibition downmodulates gene expression and protein levels of MMP-9, MMP-2, their inhibitors TIMP-1 and TIMP-2 in inflammatory cells harvested from bronchoalveolar lavage fluid (BALFs) of mice treated with bleomycin as well as in interstitial alveolar macrophages and cuboidalized epithelial alveolar cells. At the same extent, GSK-3 inhibition blunted the increased MMP-9 and MMP-2 activity induced by a pro-fibrotic stimuli in a human lung fibroblast cell line. Moreover, α-SMA protein levels, a marker of fibroblasts-to-myofibroblasts transition involved in fibrosis, was decreased in primary fibroblasts treated with TGFß following GSK-3 inhibition. Our results confirm the implication of GSK-3 in lung inflammation and fibrosis suggesting that it might play its role by modulating MMPs expression and activity, but also pushing fibroblast towards myofibroblast phenotype and therefore enhancing ECM deposition. Thus, its inhibition could represent a possible therapeutic strategy.